A method of orthogonal oligosaccharide synthesis leading to a combinatorial library based on stationary solid-phase reaction - Ako, Takuro; Daikoku, Shusaku; Ohtsuka, Isao; Kato, Rumiko; Kanie, Osamu (Chemistry, an Asian journal, 2006)
A new, efficient synthesis of oligosaccharides, which involves solid-phase reactions without mixing in combination with an orthogonal-glycosylation strategy, is described. Despite a great deal of biological interest, the combinatorial chemistry of oligosaccharides is an extremely difficult subject. The problems include 1) lengthy synthetic protocols required for the synthesis and 2) the variety of glycosylation conditions necessary for individual reactions. These issues were addressed and solved by using the orthogonal-coupling protocol and the application of a temperature gradient to provide appropriate conditions for individual reactions. Furthermore, we succeeded in carrying out solid-phase reactions with neither mechanical mixing nor flow. In this report, the synthesis of a series of trisaccharides, namely, alpha/beta-L-Fuc-(1-->6)-alpha/beta-D-Gal-(1-->2/3/4/6)-alpha/beta-D-Glc-octyl, is reported to demonstrate the eligibility of the synthetic method in combinatorial chemistry.